2011
DOI: 10.1007/s10509-011-0908-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dust acoustic waves in a charge varying complex plasma with nonthermal ions featuring Tsallis distribution

Abstract: The concept of ion nonthermality is generalized within the theoretical framework of the Tsallis thermostatistics. In this connection, a physically meaningful ion distribution function is outlined. As the nonextensive character of the nonthermal ions increases, the distribution shoulders may become less or more prominent and high energy states are less or more probable than in the extensive nonthermal case. Variable charge dust acoustic waves are then addressed. We first consider the case of adiabatic dust char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[21,38] Because no damping effect resulting from collisions between the dust and the plasma populations is involved, this shock wave is collisionless. [21,39] The latter shows the appearance of some oscillations in the shock wave profile. These oscillations (which are due to the effect of separation of charges) decrease as the ions evolve far away from their Maxwellian trapping (i.e., when 𝛼 increases).…”
Section: 2mentioning
confidence: 97%
See 1 more Smart Citation
“…[21,38] Because no damping effect resulting from collisions between the dust and the plasma populations is involved, this shock wave is collisionless. [21,39] The latter shows the appearance of some oscillations in the shock wave profile. These oscillations (which are due to the effect of separation of charges) decrease as the ions evolve far away from their Maxwellian trapping (i.e., when 𝛼 increases).…”
Section: 2mentioning
confidence: 97%
“…A result, which agrees with those already obtained by Tribeche and collaborators. [21,39] For a good understanding, we have also carried a numerical investigation over a large gamut of plasma parameters and have remarked that the collisionless damping (due to the dust charge fluctuation) is strongly related to the constant 𝛿 (see Equation (34)). In particular, we have observed that the lower values of 𝛿 favour the generation of dissipative structures, while higher values of 𝛿 are required for the existence of coherent ones.…”
Section: 2mentioning
confidence: 99%
“…In 2012, this hybrid CTDF was introduced by Benzekka and Tribeche to study the non-linear dust acoustic waves (DAWs) in complex plasmas. [35] From 2012 to 2020, various studies have been presented by using this hybrid distribution for linear and non-linear plasmas given in the Refs. [36][37][38][39][40][41][42][43][44][45] Recently, IAWs have been studied in Vasyliunas-Cairns distributed plasmas with two non-thermal parameters (𝜅, 𝛼).…”
Section: Introductionmentioning
confidence: 99%
“…One may verify that the CTDF is also a generalization of Maxwellian distribution by applying both these limits (α = 0 and q → 1) simultaneously. First, the hybrid CTDF is outlined by Benzekka and Tribeche [40] to investigate the nonlinear dust acoustic waves (DAWs) in charge varying complex plasmas. Later, Tribeche et al used this physically meaningful hybrid distribution to analyze ion-acoustic solitary waves and suggested that providing a better fit of the space observations because of the flexibility provided by the non-extensive (q) parameter [41].…”
Section: Introductionmentioning
confidence: 99%